Canakinumab to reduce deterioration of cardiac and respiratory function in SARS‐CoV‐2 associated myocardial injury with heightened inflammation (canakinumab in Covid‐19 cardiac injury: The three C study). Issue 10 (24th August 2020) - Sheng, Calvin C; Sahoo, Debasis; Dugar, Siddharth; Prada, Robier Aguillon; Wang, Tom Kai Ming; Abou Hassan, Ossama K; Brennan, Danielle; Culver, Daniel A; Rajendram, Prabalini; Duggal, Abhijit; Lincoff, A Michael; Nissen, Steven E; et al.
Abstract: Background: In patients with Covid‐19, myocardial injury and increased inflammation are associated with morbidity and mortality. We designed a proof‐of‐concept randomized controlled trial to evaluate whether treatment with canakinumab prevents progressive respiratory failure and worsening cardiac dysfunction in patients with SARS‐CoV2 infection, myocardial injury, and high levels of inflammation. Hypothesis: The primary hypothesis is that canakiumab will shorten time to recovery. Methods: The three C study (canakinumab in Covid‐19 Cardiac Injury, NCT04365153) is a double‐blind, randomized controlled trial comparing canakinumab 300 mg IV, 600 mg IV, or placebo in a 1:1:1 ratio in hospitalized Covid‐19 patients with elevations in troponin and C‐reactive protein (CRP). The primary endpoint is defined as the time in days from randomization to either an improvement of two points on a seven category ordinal scale or discharge from the hospital, whichever occurs first up to 14 days postrandomization. The secondary endpoint is mortality at day 28. A total of 45 patients will be enrolled with an anticipated 5 month follow up period. Results: Baseline characteristics for the first 20 randomized patients reveal a predominantly male (75%), elderly population (median 67 years) with a high prevalence of hypertension (80%) and hyperlipidemia (75%). CRPs have been markedly elevated (median 16.2 mg/dL) with modest elevations in high‐sensitivity troponin T (median 21 ng/L), in keeping with the concept of enrolling patients with early myocardial injury. Conclusions: The three C study will provide insights regarding whether IL‐1β inhibition may improve outcomes in patients with SARS‐CoV2 associated myocardial injury and increased inflammation.